Implementasi Teknik Relaksasi Otot Progresif pada Penderita Ostepororosis di Desa Bangun Rejo Kecamatan Tanjung Morawa Provinsi Sumatera Utara Tahun 2025 - Petra Diansari Zega; Ali Imran Sirait; Eko Murdianto; Sri Muliati Nendah; Nurcahaya Sihombing (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Osteoporosis is a metabolic bone disorder characterized by decreased bone density, resulting in brittle, porous, and easily broken bones. This condition is more common in the elderly, especially women over 60 years of age, due to hormonal changes, the aging process, and lifestyle factors. Common clinical manifestations experienced by sufferers include back pain that can interfere with daily activities and reduce quality of life. Osteoporosis treatment does not only rely on pharmacological therapy, but can also be done through non-pharmacological therapies such as progressive muscle relaxation techniques that aim to reduce muscle tension and pain perception. This study aims to determine the effect of progressive muscle relaxation techniques on pain reduction in elderly osteoporosis sufferers in Bangun Rejo Village, Tanjung Morawa District, North Sumatra Province. The research method used a quasi-experimental design with a pre-test post-test control group design. The study involved 28 elderly respondents who met the inclusion criteria, divided into two groups: an experimental group that received progressive muscle relaxation intervention and a control group that did not receive intervention. The intervention was carried out in a structured manner according to standard procedures throughout the study period. Pain levels were measured using a numeric pain scale before and after treatment. Data analysis showed a significant reduction in pain levels in the experimental group compared to the control group, with a p-value of 0.040. These results indicate that progressive muscle relaxation techniques are effective as a non-pharmacological method for reducing pain in elderly people with osteoporosis. The findings of this study are expected to provide input for healthcare professionals, particularly nurses, in developing simple, safe, and affordable interventions to improve the quality of life of elderly people with osteoporosis, as well as encourage the routine implementation of this therapy in primary and community healthcare settings.